2005
DOI: 10.1136/qshc.2004.011478
|View full text |Cite
|
Sign up to set email alerts
|

Do clinical trials improve quality of care? A comparison of clinical processes and outcomes in patients in a clinical trial and similar patients outside a trial where both groups are managed according to a strict protocol

Abstract: Background: The conventional view that participants in randomised controlled trials sacrifice themselves for the good of future patients is challenged by increasing evidence to suggest that individual patients benefit from participation in trials. Objective: To test the hypothesis that trial participants receive higher quality care and, as a consequence, have better outcomes than patients receiving guideline driven routine care. Methods: Retrospective comparative study of 408 women with pre-eclampsia all manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Our main results aligned with those of the most recent published studies [14,15,16], although the concept of an ‘inclusion benefit' differs in various ways between well-informed adults and very preterm infants. First, in addition to the study treatment, all procedures were the same in our placebo and eligible NR groups.…”
Section: Discussionsupporting
confidence: 80%
“…Our main results aligned with those of the most recent published studies [14,15,16], although the concept of an ‘inclusion benefit' differs in various ways between well-informed adults and very preterm infants. First, in addition to the study treatment, all procedures were the same in our placebo and eligible NR groups.…”
Section: Discussionsupporting
confidence: 80%
“…These benefits of being in a clinical trial are consistent with findings by others that clinical trials may improve the clinical care of patients not part of the trial through improvement in clinical protocols. 17 …”
Section: Resultsmentioning
confidence: 99%
“…However, inadequate data are available on the actual outcomes of non-participants compared with those participating in RCTs (Schmoor et al, 1996;Braunholtz et al, 2001;Burgers et al, 2002;Peppercorn et al, 2004;West et al, 2005). Although several reports and their review (Braunholtz et al, 2001) have suggested the existence of a 'trial effect', in which participants enjoy favourable outcomes, others, especially those which attempted to exclude the confounding factors, have refuted this finding (Schmoor et al, 1996;Burgers et al, 2002;Peppercorn et al, 2004;West et al, 2005).…”
mentioning
confidence: 87%
“…Several investigations have reported a favourable overall trend with trial entry (Braunholtz et al, 2001;Peppercorn et al, 2004;West et al, 2005). This 'trial effect' could derive from several factors, such as protocol effect (the way treatments are delivered), care effect (extra care related to data gathering), Hawthorne effect (changes in doctor or patient behaviour on the basis of the knowledge that they are under observation) or placebo effect (psychologically mediated benefits) (Braunholtz et al, 2001;Peppercorn et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation